Overview of the RFX-mod contribution to the international Fusion Science Program. (29th July 2015) - Puiatti, M.E.; Dal Bello, S.; Marrelli, L.; Martin, P.; Agostinetti, P.; Agostini, M.; Antoni, V.; Auriemma, F.; Barbisan, M.; Barbui, T.; Baruzzo, M.; Battistella, M.; et al.
Abstract: The RFX-mod device is operated both as a reversed field pinch (RFP), where advanced regimes featuring helical shape develop, and as a tokamak. Due to its flexibility, RFX-mod is contributing to the solution of key issues in the roadmap to ITER and DEMO, including MHD instability control, internal transport barriers, edge transport and turbulence, isotopic effect, high density limit and three-dimensional (3D) non-linear MHD modelling. This paper reports recent advancements in the understanding of the self-organized helical states, featuring a strong electron transport barrier, in the RFP configuration; the physical mechanism driving the residual transport at the barrier has been investigated. Following the first experiments with deuterium as the filling gas, new results concerning the isotope effect in the RFP are discussed. Studies on the high density limit show that in the RFP it is related to a toroidal particle accumulation due to the onset of a convective cell. In the tokamak configuration, q ( a ) regimes down to q ( a ) = 1.2 have been pioneered, with (2, 1) tearing mode (TM) mitigated and (2, 1) resistive wall mode (RWM) stabilized: the control of such modes can be obtained both by poloidal and radial sensors. Progress has been made in the avoidance of disruptions due to the (2, 1) TM by applying q ( a ) control, and on the general issue of error field control. The effect of externally applied 3D fields on plasma flow and edge turbulence, sawtooth control and runaway electron decorrelation has been analysed. The experimental program is supported by substantial theoretical activity: 3D non-linear visco-resistive MHD and non-local transport modelling have been advanced; RWMs have been studied by a toroidal MHD kinetic hybrid stability code.